Direct liquid-phase phenol-to-aniline amination using Pd/C. Issue 10 (27th April 2018) - Cuypers, Thomas; Tomkins, Patrick; De Vos, Dirk E.
Abstract : Here, we report the first direct amination of phenol with ammonia into primary anilines in the liquid phase using Pd/C. Abstract : Here, we report the first direct amination of phenol with ammonia into primary anilines in the liquid phase. For this, Pd/C was demonstrated to be the most suitable catalyst. Optimization of the reaction parameters resulted in very selective and sustainable production of primary anilines with yields of up to 95%.